A Highly Accurate and Reliable Data Fusion Framework for Guiding the Visually Impaired - Elmannai, Wafa M.; Elleithy, Khaled M. (IEEE access, 2018)
The world has approximately 253 million visually impaired (VI) people according to a report by the world health organization (WHO) in 2014. Thirty-six million people are estimated to be blind. According to WHO, 217 million people are estimated to have moderate to severe visual impairment. An important factor that motivated this research is the fact that 90% of VI people live in developing countries. Several systems were designed to improve the quality of the life of VI people and support their mobility. Unfortunately, none of these systems are considered to be a complete solution for VI people and these systems are very expensive. We present in this paper an intelligent framework for supporting VI people. The proposed work integrates sensor-based and computer vision-based techniques to provide an accurate and economical solution. These techniques allow us to detect multiple objects and enhance the accuracy of the collision avoidance system. In addition, we introduce a novel obstacle avoidance algorithm based on the image depth information and fuzzy logic. By using the fuzzy logic, we were able to provide precise information to help the VI user in avoiding front obstacles. The system has been deployed and tested in real-time scenarios. An accuracy of 98% was obtained for detecting objects and 100% accuracy in avoiding the detected objects.